Peutz–Jeghers syndrome – Be in need of vigilance: A case report - Vandana S. Tomey; Sudhir Tomey; Kewal Dhone; Tanmay Tapase (Journal of Family Medicine and Primary Care)
Peutz–Jeghar syndrome (PJS) is an inherited condition that puts people at an increased risk for developing hamarotmatous polyps in the digestive tract as well as cancers of the breast, colon, rectum, pancreas, stomach, testicles, ovaries, lung and cervix. With typical presentation, majority cases of PJS can be diagnosed in childhood. PJS is inherited by mutation in the STK II gene, also known as LKB1 gene. We describe the case of a 14-year-old male who presented to us with recurrent abdominal pain, vomiting and weight loss associated with growth failure. Classic melanin spots were present on lips and buccal mucosa. Diagnosis of PJS was established via clinical history, examination, CT scan, and endoscopy revealing the need for laparotomy for bowel obstruction secondary to chronic intermittent intussusception, enterotomy for small polyps. Polyp histopathology was consistent with hamartomatous polyps of PJS.